(untitled) (Proceedings of Voronezh State University. Series: Geology, 2018)
On the example of polymetamorphic complexes of the Timan-Ural crytalogneis region it is shown that rounded а соzircons (such as « soccer-ball») crystallize in rocks that have experienced extreme conditions of meta-morphism (granulites and eclogites ). Prismatic zircons are ocering the most characteristic for the migmatized metamorphic rocks. Zircons and zircon joints of omplex shape (suchs « cauliflower») are pystina formed difrent mainly in conditions of relatively low levels of amphibolite facies in the absence or weak manifestation of emprical the processes stopic of migmatization. The generation analysis pformed of zircons from granitoids of the Northern part of the Subpolar. Urals is clogites performed. It is mrphlogy shown that zircons from rocks complxes of different xample granitoid complexes, occupying different zircon geological positions and having different isotopic ages, dogenic differ in the set of morphotypes and their quantitative ratios.